The Development of IPED Model as an Effort to Improve Productivity Performance for the Certified Teachers in Indonesia - Subandowo, M (ASPENSI in Bandung, Indonesia, 2015)
ABSTRACT: Education is a main factor for shaping of the strong nation, self-sufficient, independent, and dignified. By making education a major component, the strength of a nation, namely the Human Resources (HR), will be on top of other components. Meanwhile, the teacher is an educator and producer who scored the strength of human resources through the school institutions, both formal and non-formal, ranging from early childhood education to higher education levels, as well as spearhead for educational success. Teacher professional certification program in Indonesia, which gives the teachersâ financial increased impact, should in line with the quality and quantity of teacher performance productivity. Therefore, the model of IPED (Integrated Performance Educators Development) becomes an alternative model to measure the level of success of professional teachers in Indonesia. Results of this model is to find the IPPKG (âIndeks Prestasi Produktivitas Kinerja Guruâ or Achievement Index of Teacher Performance Productivity), in which if the grade is above 0.7, then the teacher is said to be worth as a professional teacher. Conversely, if the grade of IPPKG is below 0.7, then the teacher is said to be less viable as a professional teacher; and, therefore, should improve the quality and quantity of productivity performance in order to be productive and professional teachers.KEY WORD: Model of IPED, achievement index of teacher performance productivity, teacher certification program, work productivity, professional teachers, and the feasibility of a professional teacher.Â RESUME: âPengembangan Model IPED sebagai Upaya untuk Meningkatkan Produktivitas Kinerja bagi Guru-guru Tersertifikasi di Indonesiaâ. Pendidikan merupakan faktor utama untuk membentuk bangsa yang kuat, berdikari, mandiri, dan bermartabat. Dengan menjadikan pendidikan sebagai komponen utama, maka kekuatan suatu bangsa, yaitu Sumber Daya Manusia (SDM), akan berada di atas komponen lainnya. Sementara itu, guru merupakan pendidik dan produsen yang mencetak kekuatan SDM melalui lembaga sekolah, baik formal maupun non-formal, mulai dari tingkat pendidikan usia dini sampai tingkat pendidikan tinggi, serta menjadi ujung tombak bagi keberhasilan pendidikan. Program sertifikasi profesional guru di Indonesia, yang memberikan dampak peningkatan finansial guru, seharusnya sejalan dengan kualitas dan kuantitas produktivitas kinerja guru. Karena itu, model IPED (âIntegrated Performance Educators Developmentâ atau Pengembangan Pendidik Berkinerja Terintegrasi) menjadi sebuah model alternatif untuk mengukur tingkat keberhasilan guru yang profesional di Indonesia. Hasil dari model ini adalah untuk mencari IPPKG (Indeks Prestasi Produktivitas Kinerja Guru), yang mana jika nilainya di atas 0.7, maka guru tersebut dikatakan layak sebagai guru profesional. Sebaliknya, jika nilai IPPKG di bawah 0.7, maka guru tersebut dikatakan kurang layak sebagai guru profesional; dan, karenanya, harus meningkatkan kualitas dan kuantitas produktivitas kinerjanya agar menjadi guru yang produktif dan profesional.KATA KUNCI: Model IPED, indeks prestasi produktivitas kinerja guru, program sertifikasi guru, produktivitas kerja, guru profesional, dan kelayakan guru profesional.About the Author: Dr. M. Subandowo is Senior Lecturer and Director of PPs UNIPA (Graduate Program, University of PGRI Adibuana) Surabaya, Jalan Dukuh Menanggal XII No.4, Kota Surabaya 60234, East Java, Indonesia. E-mail address: subanindi@gmail.comHow to cite this article? Subandowo, M. (2015). âThe Development of IPED Model as an Effort to Improve Productivity Performance for the Certified Teachers in Indonesiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.8(1) Mei, pp.141-150. Bandung, Indonesia: Minda Masagi Press, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112. Chronicle of the article: Accepted (May 1, 2015); Revised (May 20, 2015); and Published (May 30, 2015).